High resolution modeling of dense water formation in the north‐western Mediterranean during winter 2012–2013: Processes and budget. Issue 7 (31st July 2016) - Estournel, Claude; Testor, Pierre; Damien, Pierre; D'Ortenzio, Fabrizio; Marsaleix, Patrick; Conan, Pascal; Kessouri, Faycal; Durrieu de Madron, Xavier; Coppola, Laurent; Lellouche, Jean‐Michel; Belamari, Sophie; Mortier, Laurent; et al.
Abstract: The evolution of the stratification of the north‐western Mediterranean between summer 2012 and the end of winter 2013 was simulated and compared with different sets of observations. A summer cruise and profiler observations were used to improve the initial conditions of the simulation. This improvement was crucial to simulate winter convection. Variations of some parameters involved in air ‐ sea exchanges (wind, coefficient of transfer used in the latent heat flux formulation, and constant additive heat flux) showed that the characteristics of water masses and the volume of dense water formed during convection cannot be simply related to the time‐integrated buoyancy budget over the autumn ‐ winter period. The volume of dense water formed in winter was estimated to be about 50, 000 km 3 with a density anomaly larger than 29.113 kg m −3 . The effect of advection and air/sea fluxes on the heat and salt budget of the convection zone was quantified during the preconditioning phase and the mixing period. Destratification of the surface layer in autumn occurs through an interaction of surface and Ekman buoyancy fluxes associated with displacements of the North Balearic front bounding the convection zone to the south. During winter convection, advection stratifies the convection zone: from December to March, the absolute value of advection represents 58 % of the effect of surface buoyancy fluxes. Key Points: Realistic simulation of winter convection and dense water formation Correction of initial and boundary conditions improves the simulation Sensitivity studies to air ‐ sea fluxes are characterized